Income sharing and sharing norms: evidence from lab and field experiments - Fromell, Hanna C. (2018)
There is ample evidence that people act to ensure the well-being of others by sharing their income. Extensive research shows of the many positive aspects associated with income sharing and the so called “sharing norms” that serve to enforce this practice as well as of how one can further encourage income sharing and sharing norms. In this thesis, I present experimental evidence illustrating that, in some cases, income sharing and sharing norms may have negative consequences for some individuals. The evidence presented also shows that people’s desire to share income with others may in fact be more robust than sometimes proposed in the literature. Chapter 2 is based on a field experiment in rural communities in Kenya. It shows that individuals in these communities live by sharing norms that clearly prescribe them to share their income with others at the expense of personal savings. For women, these norms are more proscriptive of savings if information about income is public to others in their community rather than private. These norms, and their interaction with public information, systematically affect individuals’ actual savings in interest-bearing bank accounts. Chapter 3 shows that having the possibility to share income with others can put people in a choice dilemma that is mentally demanding and costly. A lab experiment is used that lets participants make decisions as dictators in modified dictator games that expose them to tradeoffs between their self-interest and the interest of others. Other participants make similar decisions with the difference that there is no tradeoff between their own self-interest and the interest of others. The study shows that participants who have been exposed to such tradeoffs, on average, perform worse in a task that measures cognitive resources and willpower compared to participants who have not been exposed to tradeoffs. Chapter 4 shows that individuals’ willingness to share income with others may be more robust than sometimes suggested in previous literature. Different versions of the dictator game are used to investigate individuals’ willingness to help others (by sharing their income) in an appeal-for-help situation in which several individuals have the possibility to share income with a person with lower income and where at most one of them can do so. As a group, individuals make the recipient of the dictator game better off when all, rather than only one, of them are able to share their income. This evidence challenges a common interpretation of behaviour in related literature, which assumes reduced concerns for others and an erosion of pro-social values when the responsibility to help lies on several potential helpers.